Money Laundering in Pakistan: Combating Strategies and Preventions - Imran, Muhammad; Murtiza, Ghulam; Akbar, Muhammad Sulyman (Annals of Human and Social Sciences, 2024)
This research seeks to analyze the present legal and regulatory frameworks in Pakistan with regard to their efficiency in combatting money laundering. It will also take a look at the obstacles and complexity that come with these efforts. Pakistan encounters a unique mix of difficulties due to its geopolitical location, leadership problems, and structural deficiencies in its financial and legal institutions. An investigation of anti-money laundering laws in Pakistan, as well as a literature research, interviews with relevant experts and stakeholders, and primary and secondary sources make up this study's thorough methodology. Lack of interagency coordination, political influence on law enforcement, and legal loopholes are some of the serious issues highlighted by the findings in relation to Pakistan's anti-money laundering (AML) system. In order to strengthen Pakistan's AML efforts, the report suggests a multi-pronged approach. This approach may incorporate the finest practices of prosperous nations.